Peran Website Bimbingan Konseling dalam Menangani Pelanggaran Tata Tertib Siswa dengan Tinjauan Psikologis Pendidikan di SMK 5 Palembang - S, Asiawatie; Abdullah, Zet; Rahma Sari, Indah; Mahmud, Mahmud; Aryo Pramuditho, Anggoro (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
The development of information technology provides great opportunities for the world of education, especially in supporting Guidance and Counselling (BK) services. This study aims to examine the role of the Guidance and Counselling website in handling student disciplinary violations at the high school/vocational school level with a psychological approach. The method used in this study is descriptive qualitative with data collection techniques through interviews, observations, and documentation in several high schools/vocational schools that have implemented a website-based BK system. The results of the study indicate that the use of the BK website can increase the effectiveness of communication between BK teachers, students, and parents, as well as facilitate data collection and monitoring of violation cases. In addition, the psychological approach applied through features such as self-assessment, online counselling, and digital education has a positive impact on students' understanding of the consequences of their behaviour. Thus, the BK website not only functions as an administrative tool, but also as a preventive and rehabilitative media in handling student disciplinary violations. This study recommends the development of a more interactive and integrated digital BK system to support sustainable student character building